Vascularization of the Long Flexor Tendon - (:unkn) unknown (My University, 1994)
The arterial supply of the long flexor tendon of the index and ring fingers were studied morphologically on 36 cadaver hands. Our studies, showed that the long flexor tendons were supplied by two main sources. Primarily by small arteries which ran in the vinculum longum and vinculum brevis and reached the dorsal surface of the tendon. Also by small intrinsic longitudinal vessels which ran parallel to the collagenous fibers of the tendon and extended from the muscular attachment of the long flexor tendons. No morphological difference on the vascularization of the index and ring fingers were observed. © 1994, Editorial Board of Okajimas Folia Anatomica Japonica. All rights reserved.
Keywords: flexor; Morphological; Tendon; Vascularization